2014
DOI: 10.3233/nre-141056
|View full text |Cite
|
Sign up to set email alerts
|

Transitions between SNF and home-based care in patients with multiple sclerosis

Abstract: OBJECTIVES: To assess patient characteristics and risk factors associated with care transitions between skilled nursing facility (SNF) and home care for patients with multiple sclerosis (MS) in an effort to improve outcomes and optimize patient care pathways. BACKGROUND: MS is a chronic neurologic illness of younger adults that is associated with physical disability, cognitive impairment and a high need for supportive services. METHODS:The study was based on the 2005 Nursing Home Minimum Data Set and the Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Bowel and bladder incontinence are often cited as most frequent dysfunction along with cognitive dysfunction in PwMS who reside in nursing homes. 49 Monitoring aging MS population The outcome measures often used to assess MS patients may not be sufficient or specific to the problem encountered by the aging PwMS. A recent cross-sectional study evaluated a cohort of 346 MS patients enrolled in the New York State Multiple Sclerosis Consortium (NYSMSC), mean age of 67.7 ± 5.5 years with mean duration of symptoms being 29.9 ± 10 years.…”
Section: Psychological and Cognitive Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowel and bladder incontinence are often cited as most frequent dysfunction along with cognitive dysfunction in PwMS who reside in nursing homes. 49 Monitoring aging MS population The outcome measures often used to assess MS patients may not be sufficient or specific to the problem encountered by the aging PwMS. A recent cross-sectional study evaluated a cohort of 346 MS patients enrolled in the New York State Multiple Sclerosis Consortium (NYSMSC), mean age of 67.7 ± 5.5 years with mean duration of symptoms being 29.9 ± 10 years.…”
Section: Psychological and Cognitive Problemsmentioning
confidence: 99%
“…Bowel and bladder incontinence are often cited as most frequent dysfunction along with cognitive dysfunction in PwMS who reside in nursing homes. 49…”
Section: Psychological and Cognitive Problemsmentioning
confidence: 99%
“…Cognitive disability has been associated with greater risk for less self-efficacy ( 42 ), and lower quality of life ( 47 ) not only among people with IDD but those with age-related and/or physical disabilities. It is related to the duration a person with age-related disability spend in hospital-level care ( 48 , 49 ) and has been shown to mediate the relationship between physical activity and lower blood pressure ( 50 ). Among individuals with IDD, level of intellectual disability, a measure directly related to cognitive ability, has been associated with lower levels of self-determination ( 51 ), less choice-making ( 12 ) and lower levels of community-based employment ( 52 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Noyes et al 6 showed that although the cost for a skilled nursing facility is high, the staff-to-resident ratio is also high, leading to appropriate individualized care given to patients with MS and possibly resulting in a positive effect physically and psychologically. Interestingly, a study comparing daily costs incurred by skilled nursing facilities showed that there were no significant variations in daily cost for facilities with a greater proportion of patients with MS among their residents compared with those with fewer patients with MS. 12 However, evidence suggests that most nursing home directors were unaware of the guidelines developed by the National Multiple Sclerosis Society to aid in the care of nursing home residents with MS. 17 More specifically, these guidelines suggest that, at minimum, rehabilitation professionals should be available to residents with MS to "maximize independence, mobility, and quality of life."…”
Section: Discussionmentioning
confidence: 99%
“…5 Home-based care can include personal assistance (eg, toileting and bathing), homemaking, aid in mobility and leisure activities, 1 or symptom management (eg, administering corticosteroid injections and changing catheters during an episode of acute exacerbation of symptoms to avoid hospital admission). 6 is primarily wheelchair-bound. The final sample included 924 nonambulatory patients for analysis.…”
mentioning
confidence: 99%